CDSD-296, high resolution carbon dioxide spectroscopic databank: Version for atmospheric applications. (February 2015) - Tashkun, S.A.; Perevalov, V.I.; Gamache, R.R.; Lamouroux, J.
Abstract: We present an atmospheric version, CDSD-296, of the carbon dioxide spectroscopic databank (CDSD). The databank contains the calculated line parameters (positions, intensities, air- and self-broadened half-widths, coefficients of temperature dependence of air-broadened half-widths and air pressure-induced line shifts) of the twelve stable isotopic species of CO2 . The reference temperature is T ref =296 K and the intensity cutoff is I cut =10 − 30 cm − 1 /(molecule cm − 2 ). More than 500, 000 lines covering the 6–14, 075 cm −1 spectral range are included in CDSD-296. The databank has been generated within the framework of the method of effective operators and based on the global weighted fits of spectroscopic parameters (parameters of the effective Hamiltonians and effective dipole moment operators) to observed data collected from the literature. The fitted models are able to reproduce known measured positions and intensities with accuracies compatible with measurement uncertainties. The line-shape parameters originate from the recent theoretical and semi-empirical calculations. Comparisons of CDSD-296 with HITRAN-2012, GEISA-2011, and the AMES line lists are also given. Graphical abstract: Highlights: CDSD-296 is aimed at atmospheric applications. CDSD-296 contains data of all 12 stable CO2 isotopologues. CDSD-296 is based on global fits of measured line positions and intensities. CDSD-296 contains calculated line parameters for the 6–14, 075 cm −1 spectral range.